Evidence on Cost-sharing in Health Care : Applications to Hungary : Executive Summary - World Bank (Washington, DC, 2013)
This study, done at the request of the Hungarian government, presents evidence on cost-sharing in the health sector, and its application in Hungary. It presents results on the impact of cost-sharing on revenues in health facilities and insurance, financial sustainability, informal payments, overall service use, and equity in access. Five keyfindings emerge: cost-sharing could lead to a reduction in unnecessary care provided to insured patients who do not have to pay the full price of care; cost-sharing could help reduce informal payments and keep patient payments in the system; cost-sharing with exemption policies are a prerequisite to provide equity in access to care; cost-sharing could support cost containment strategies; experience from OECD countries provides examples of successful cost-sharing policies. Based on these findings. the study recommends that Hungary continues to monitor and evaluate the impact of cost-sharing on access, to identify possible negative effects on equity in service use. In Hungary, financial incentives through the provider payment system could eventually support the effect of the government supply-side strategy. Such financial incentives could be set to providers through capitation payment to reward better quality of care, and Diagnosis Related Group (DRG) payments with expenditure ceilings with strict utilization review and quality assurance control to set an incentive for efficient provision of care.